化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
2个回答
原式=(cosθ-tan²θcosθ)/(1-tanθ)
=cosθ(1+tanθ)(1-tanθ)/(1-tanθ)
=cosθ+sinθ
相关问题
化简sinθ(1+tanθ)+cosθ(1+cotθ)
求证:tanθ*sinθ/tanθ-sinθ=1+cosθ/sinθ
试证:tanθ(1+sinθ)+sinθtanθ(1+sinθ)−sinθ=[tanθ+sinθ/tanθsinθ].
三角函数:1+tan²θ=tanθ/sinθcosθ
求证sinθ(1+tanθ)+cosθ(1+1/tanθ)=1/sinθ+1/cosθ
若兀/4tanθB.cosθ>tanθ>sinθC.sinθ>tanθ>cosθD.tanθ>sinθ>cosθ
求证:(1-tanθ)/(1+tanθ)=(1-2sinθcosθ)/(cos2θ-sin2θ)
化简sin(θ−5π)tan(3π−θ)•1tan(θ−3π2)tan(π2−θ)•cos(8π−θ)sin(−θ−4π
求证:2(cos θ -sin θ )/(1+sinθ +cosθ)=tan(∏/4- θ /2)-tan(θ /2)
1/cos²θ - tan²θ - sin²θ